1962
DOI: 10.1152/ajplegacy.1962.202.3.461
|View full text |Cite
|
Sign up to set email alerts
|

Growth of hamsters during continual centrifugation

Abstract: Female Syrian hamsters have been subjected to continual centrifugation for a period of 4 weeks at four or five times the earth's gravity. Animals were 5 weeks of age at the onset of exposures. Although an increased gravitational field curtails body growth, certain organs were found to show an increase in their relative mass when compared to control littermates. The heart, diaphragm, gastrocnemius muscle, lungs, kidney, and head showed a relative increase in mass, and the femur bones of centrifuged hamsters sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Hypergravity hamsters weighed less than hamsters conceived and born in normal gravity (HL and HS hamsters vs. CON and ROT hamsters), which is in accordance with earlier studies concerning the effect of hypergravity on body weight in rodents [3,22]. Rotation in the centre of the centrifuge (ROT group) did not result in a body weight decrease, a finding also reported by Martin [18].…”
Section: Discussionsupporting
confidence: 91%
“…Hypergravity hamsters weighed less than hamsters conceived and born in normal gravity (HL and HS hamsters vs. CON and ROT hamsters), which is in accordance with earlier studies concerning the effect of hypergravity on body weight in rodents [3,22]. Rotation in the centre of the centrifuge (ROT group) did not result in a body weight decrease, a finding also reported by Martin [18].…”
Section: Discussionsupporting
confidence: 91%
“…Body mass loss has been previously observed in centrifuging studies using chickens (Smith et al 1959), mice (Wunder 1960), hamsters (Briney and Wunder 1962) and rats (Oyama and Platt 1965). It has been suggested that major cause of loss of body mass could be the decreased amount of fatty tissue in the presence of muscle hypertrophy (Amtmann and Oyama 1973;Keil 1969).…”
Section: Discussionmentioning
confidence: 89%
“…Since body weight is evaluated as b.w. = ma, where m = body mass, and a = acceleration (typically, a is the acceleration due to gravity), a desired, simulated increase in body weight can be accomplished by producing an appropriate increase in acceleration.The studies in the literature on the effects of hypergravity on bone growth are consistent in using accelerations greater than 2.OG (an effective doubling of body weight), and in reporting a repression of bone growth under hypergravity (Amtmann and Oyama, 1976; Briney and Wunder, 1962;Smith 1975Smith ,1977; and many others). However, when lambs were loaded by weights totaling 40% of total body weight (1.4G) positive bone growth effects were reported (Tulloh and Romberg, 1963).…”
mentioning
confidence: 68%
“…The studies in the literature on the effects of hypergravity on bone growth are consist-ent in using accelerations greater than 2.OG (an effective doubling of body weight), and in reporting a repression of bone growth under hypergravity (Amtmann and Oyama, 1976; Briney and Wunder, 1962;Smith 1975Smith ,1977; and many others). However, when lambs were loaded by weights totaling 40% of total body weight (1.4G) positive bone growth effects were reported (Tulloh and Romberg, 1963).…”
mentioning
confidence: 99%